A guide to online course design strategies for student success - Stavredes, Tina; Herder, Tiffany 1981- (San Francisco, California Jossey-Bass, 2014)
"This book offers a much-needed resource for faculty and professional staff to build quality online courses by focusing on quality standards in instructional design and transparency in learning outcomes in the design of online courses. It includes effective instructional strategies to motivate online learners, help them become more self-directed, and develop academic skills to persist and successfully complete a program of study online. It also includes a more in-depth understanding of instructional design principles to support faculty as they move their face-to-face courses to the online environment"--Provided by publisher.
Exhibits and figures -- Preface -- About the authors -- Part 1. An introduction to persistence and quality design. 1. Quality design to support learner persistence defining persistence ; 2 The instructional design process backward design framework instructional design process -- Part 2. Analysis of learners and learning outcomes. 3. Analysis of online learner characteristics and needs online learners characteristics learner persistence learner needs ; 4. Analysis of learning outcomes and competencies -- Part 3. Design of course assessments and sequence. 5. Design of course assessments ; 6. Sequence of instruction -- Part 4. Design of instructional strategies. 7. Foundations of transformative learning principles of learning ; 8. Selection of instructional materials ; 9. Design of effective course activities -- Part 5. Development of instruction. 10. Development of instructional materials ; 11. Organizing the course environment -- Part 6. Implementation and evaluation. 12. Course evaluations and maintenance -- Final remarks -- References -- Index.
Keywords: Web-based instruction -- Design; College teaching; Distance education